(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Ajaswagandhadhi Lehyam is a Plant Preparation used in traditional Medicinal practice as a Nervine Tonic. Toxicity test has to be done to evaluate the toxic compounds present in Ajaswagandhadhi Lehyam. This study involves the acute and sub-acute toxicity study of Ajaswagandhadhi Lehyam in male Wistar rats. Ajaswagandhadhi Lehyam from Kottakal is preferred for the study. Haemotological, Biochemical and various other parameters were observed to find any evidence of acute and sub-acute toxicity of Ajaswagandhadhi Lehyam.